Standardized laparoscopic central hepatectomy based on hilar caudal view and root approach of the right hepatic vein. (10th October 2019) - Rotellar, Fernando; Martí‐Cruchaga, Pablo; Zozaya, Gabriel; Tuero, Carlota; Luján, Juan; Benito, Alberto; Hidalgo, Francisco; López‐Olaondo, Luis; Pardo, Fernando
Abstract : Central hepatectomy is one of the most difficult procedures to perform laparoscopically. Rotellar and colleagues described a standardized technique, tailored specifically to laparoscopy, which facilitates its safe performance based on three principles: no liver mobilization, initial Glissonean control (based on Laennec's capsule approach) and root approach of the major veins.